Arabidopsis MDN1 Is Involved in the Establishment of a Normal Seed Proteome and Seed Germination - Li, Peng-Cheng; Ma, Jun-Jie; Zhou, Xi-Meng; Li, Guang-Hui; Zhao, Chuan-Zhi; Xia, Han; Fan, Shou-Jin; Wang, Xing-Jun (Frontiers in Plant Science, 2019)
Seed germination and formation are the beginning and ending, respectively, of a plant life cycle. These two processes are under fine regulation by the internal genetic information. Previously, we demonstrated that Arabidopsis MIDASIN 1 (MDN1) is required for ribosome biogenesis, and its dysfunction leads to pleiotropic developmental phenotypes, including impaired embryogenesis and slow seed germination. In this study, we further found that the weak mutant of MDN1, mdn1-1, exhibits an increased seed size phenotype. Seed proteomic analysis reveals that a number of proteins involved in seed development and response to external environments are mis-regulated by the MDN1 dysfunction. Many 2S Seed Storage Proteins (SSPs) and Late Embryogenesis Abundant (LEA) proteins are over-accumulated in the dry seeds of mdn1-1. Further, some genes encoding seed storage reserves are also upregulated in mdn1-1 seedlings. More interestingly, ABSCISIC ACID-INSENSITIVE 5 (ABI5) is over-accumulated in mdn1-1 seeds, and the loss of its function partially rescues the low seed germination rate of mdn1-1. Together, this study further demonstrates that MDN1 is essential for establishing a normal seed proteome, and its mutation triggers ABI5-mediated repression of seed germination.